Prevalence and outcomes of diaphragmatic dysfunction assessed by ultrasound technology during acute exacerbation of COPD: A pilot study. Issue 2 (14th October 2016) - Antenora, Federico; Fantini, Riccardo; Iattoni, Andrea; Castaniere, Ivana; Sdanganelli, Antonia; Livrieri, Francesco; Tonelli, Roberto; Zona, Stefano; Monelli, Marco; Clini, Enrico M.; Marchioni, Alessandro
ABSTRACT: Background and objective: The prevalence and clinical consequences of diaphragmatic dysfunction (DD) during acute exacerbations of COPD (AECOPD) remain unknown. The aim of this study was (i) to evaluate the prevalence of DD as assessed by ultrasonography (US) and (ii) to report the impact of DD on non‐invasive mechanical ventilation (NIV) failure, length of hospital stay and mortality in severe AECOPD admitted to respiratory intensive care unit (RICU). Methods: Forty‐one consecutive AECOPD patients with respiratory acidosis admitted over a 12‐month period to the RICU of the University Hospital of Modena were studied. Diaphragmatic ultrasound (DU) was performed on admission before starting NIV. A change in diaphragmatic thickness (ΔTdi) less than 20% during spontaneous breathing was considered to confirm the presence of dysfunction (DD+). NIV failure and other clinical outcomes (duration of mechanical ventilation MV, tracheostomy, length of hospital stay and mortality) were recorded. Results: A total of 10 out of 41 patients (24.3%) presented DD+, which was significantly associated with steroid use ( P = 0.002, R‐squared = 0.19). DD+ correlated with NIV failure ( P < 0.001, R‐squared = 0.27), longer intensive care unit (ICU) stay ( P = 0.02, R‐squared = 0.13), prolonged MV ( P = 0.023, R‐squared = 0.15) and need for tracheostomy ( P = 0.006, R‐squared = 0.20). Moreover, the Kaplan–Meyer survival estimates showed that NIV failure (log‐rank test P value = 0.001, HR = 8.09 (95% CI: 2.7–24.2)) and mortality in RICU (log‐rank test P value = 0.039, HR = 4.08 (95% CI: 1.0–16.4)) were significantly associated with DD+. Conclusion: In hospitalized AECOPD patients submitted to NIV, severe DD was seen in almost one‐quarter of patients. DD may cause NIV failure, and impacts on the use of clinical resources and on the patient's short‐term mortality. Abstract : In this pilot study, we assessed diaphragmatic dysfunction (DD) by ultrasonography in severe acute exacerbations of COPD (AECOPD) patients admitted in intensive care unit for severe hypercapnic respiratory failure. We found that severe DD is reported in almost one‐quarter of AECOPD patients. This factor may cause non‐invasive mechanical ventilation failure, and impact short‐term mortality.